2014
DOI: 10.1093/ckj/sfu025
|View full text |Cite
|
Sign up to set email alerts
|

Crystalloid glomerulopathy in monoclonal gammopathy of renal significance (MGRS)

Abstract: We report a case of monoclonal gammopathy of renal significance in a 63-year-old man who presented with nephrotic-range proteinuria and renal insufficiency. The kidney biopsy showed a membranoproliferative glomerulonephritis pattern with extensive crystalloid deposits in the glomerular capillary endothelial cells and very few in the tubular epithelial cells. The immunoperoxidase staining showed kappa light chain restriction. Subsequently, the bone marrow showed 6% plasma cells which confirmed the diagnosis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 15 publications
0
9
1
Order By: Relevance
“…5 Vankalakunti et al reported a rare case of monoclonal gammopathy of renal significance, which had similarities with our case; their case presented monoclonal LC inclusions predominantly in the glomerular endothelial cells and showed a good response to bortezomib. 6 However, their case demonstrated heavy proteinuria with renal insufficiency, and their renal biopsy revealed a membranoproliferative glomerulonephritis with crystalloid formation in glomerular endothelial cells, 6 which were different from ours. Although considered an atypical finding in MM, this presentation was considered to be associated with MM in the current patient because the urinary abnormalities improved after the treatment for MM.…”
Section: Discussioncontrasting
confidence: 72%
“…5 Vankalakunti et al reported a rare case of monoclonal gammopathy of renal significance, which had similarities with our case; their case presented monoclonal LC inclusions predominantly in the glomerular endothelial cells and showed a good response to bortezomib. 6 However, their case demonstrated heavy proteinuria with renal insufficiency, and their renal biopsy revealed a membranoproliferative glomerulonephritis with crystalloid formation in glomerular endothelial cells, 6 which were different from ours. Although considered an atypical finding in MM, this presentation was considered to be associated with MM in the current patient because the urinary abnormalities improved after the treatment for MM.…”
Section: Discussioncontrasting
confidence: 72%
“…Both CSH and crystalglobulinemia are most frequently seen in the setting of MM and lymphoproliferative disorders, and they are only rarely seen in MGRS. 48,[50][51][52][53][54][55]…”
Section: Clinical Presentationmentioning
confidence: 99%
“…61 A subset of patients with C3 glomerulopathy have an associated MIg. [62][63][64] MIgs in the setting of C3 glomerulopathy likely act as autoantibodies to complement regulatory proteins, such as factor H or the C3 convertase (i.e., behaving as a C3 nephritic factor), thereby increasing the t 1/2 of the C3 convertase, [52][53][54] resulting in DDD, C3GN, or rarely, atypical hemolytic uremic syndrome. 65 Indeed, in a recent large study, complement evaluation revealed C3 nephritic factor in 45.8% of patients with MIg-associated C3 glomerulopathy, whereas pathogenic variants in complement genes were rare.…”
Section: Mig-associated Renal Disease With No Mig On If Studies (Indimentioning
confidence: 99%
“…Crystals are located within the cytoplasm of proximal tubular epithelial cells, although occasional intraluminal crystalline casts can also be seen . Other cell types within the kidney can accumulate light chain crystals including podocytes, endothelial cells, and histiocytes . Light chain podocytopathy is particularly uncommon and was present in only 3 of 46 cases reported by Stokes et al .…”
Section: Discussionmentioning
confidence: 98%